Valorisation of the biological activities of some North African Saharan plant species - (:unkn) unknown (My University, 2016)
The Saharan desert is one of the most unfavorable areas, to the plant life. However, a small number of plants possesses both morphological and ecophysiological mechanisms ensuring their survival in the arid soil and on the sand dunes.It can be estimated that the secondary metabolism biosynthesizes considerable amounts of bioactive compounds, meant to ensure the development and the continuity of these species.The pharmacological properties of saharan plant extracts may bring benefits in the healing of certain microbial or proliferative diseases or contributes to the supply of antioxidants activities.The study of toxic properties is meant to enrich the knowledge of Saharan plants’bioactive potential.The biological activities of Anthyllis henoniana Coss., Centropodia forskalii (Vahl)Cope, Cornulaca monacantha Delile, Ephedra alata var. alenda (Stapf.) Trabut,Euphorbia guyoniana Boiss & Reut., Henophyton deserti Coss. & Durieu, Helianthemum confertum Dunal, Moltkiopsis ciliata (Forssk.) I.M.Johnst. and Spartidium saharae (Coss.& Durieu) Pomel have been studied. It can be seen that these species possess interesting properties, capitalized in the treatment of some human diseases. But, on the other hand in certain concentrations, extracts from these species may exhibit toxic effects onorganisms.Despite the extreme conditions, the Saharan desert represents the area of development for some valuable plant species, whose scientific knowledge is necessary.
Keywords: African Research